2013
DOI: 10.1139/cjfas-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Estimating occupancy and abundance of stream amphibians using environmental DNA from filtered water samples

Abstract: Environmental DNA (eDNA) methods for detecting aquatic species are advancing rapidly, but with little evaluation of field protocols or precision of resulting estimates. We compared sampling results from traditional field methods with eDNA methods for two amphibians in 13 streams in central Idaho, USA. We also evaluated three water collection protocols and the influence of sampling location, time of day, and distance from animals on eDNA concentration in the water. We found no difference in detection or amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
648
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(690 citation statements)
references
References 18 publications
36
648
6
Order By: Relevance
“…Meanwhile, a Minnesota, USA lake study of Common Carp found similar results, with rate of detection and eDNA concentration correlating positively with fish abundance (Eichmiller et al 2014). Similar correlations have also been found with multiple amphibian species in Idaho streams (Pilliod et al 2013) and European ponds (Thomsen et al 2012a). Metagenetic analysis of soils at zoos and farms (i.e.…”
Section: Estimation Of Organism Abundancementioning
confidence: 56%
“…Meanwhile, a Minnesota, USA lake study of Common Carp found similar results, with rate of detection and eDNA concentration correlating positively with fish abundance (Eichmiller et al 2014). Similar correlations have also been found with multiple amphibian species in Idaho streams (Pilliod et al 2013) and European ponds (Thomsen et al 2012a). Metagenetic analysis of soils at zoos and farms (i.e.…”
Section: Estimation Of Organism Abundancementioning
confidence: 56%
“…However, how these parameters might affect eDNA detection probabilities, remains unclear (Pilliod et al, 2014). Site occupancy models provide a means to account for imperfect detection of various sampling methods (Pollock et al, 2002;Andrew Royle, & Dorazio, 2008;Pilliod, Goldberg, Arkle, & Waits, 2013) including eDNA methods (Schmidt et al, 2013). Occupancy models can be used to study the effects of various abiotic and biotic factors that influence detection probabilities (both in the field and in the laboratory), and to determine the number of visits, number of samples and volume of water needed to be confident that a species is absent from a site (Schmidt et al, 2013).…”
Section: Perspective and Future Of Ednamentioning
confidence: 99%
“…Analysis of environmental DNA (eDNA) is likely to become a revolutionary tool to increase both spatial and temporal scales of monitoring datasets for species of concern (Dejean et al 2012;Jerde et al 2011Jerde et al , 2013Lodge et al 2012;Mahon et al 2013;Pilliod et al 2013;Thomsen et al 2012a). The eDNA method detects traces of DNA in cellular or extracellular form from sources such as feces, secreted mucous membranes, gametes, and skin cells (Haile et al 2009;Lydolph et al 2005;Taberlet et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The eDNA method detects traces of DNA in cellular or extracellular form from sources such as feces, secreted mucous membranes, gametes, and skin cells (Haile et al 2009;Lydolph et al 2005;Taberlet et al 2012). In addition to increasing the probability of detection of aquatic species compared to some traditional survey methods (Dejean et al 2012;Jerde et al 2011;Pilliod et al 2013;Smart et al 2015), using eDNA might also increase the observation time windows for surveys, enabling multispecies surveys and reducing the need for extensive taxonomic expertise and financial resources.…”
Section: Introductionmentioning
confidence: 99%